Medicine, the heart and accordion music (2014)
There are many musical genres which cover different aspects of medicine, and especially the heart, as a very important organ in bodily economy, metaphorically related to the expression and genesis of some emotions like love, anger, hate. The Vallenato music, born in the northern Colombian coast, is not an exception.Conclusions: The Vallenato music, as well as many other popular music genres, sing to the doctors and the heart, this latter being, in a poetic context, a depositary of emotions and capable of making one lovesick. © 2014 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular. Published by Elsevier España, S.L. All rights reserved.